Insights into the pathogenesis of varicella viruses - Sorel, Océane (Curr Clin Microbiol Rep, 2019)
PURPOSE OF REVIEW: Varicella zoster virus (VZV) is a highly contagious, neurotropic alpha herpes virus that causes varicella (chickenpox). VZV establishes lifelong latency in the sensory ganglia from which it can reactivate to induce herpes zoster (HZ), a painful disease that primarily affects older individuals and those who are immune-suppressed. Given that VZV infection is highly specific to humans, developing a reliable in vivo model that recapitulates the hallmarks of VZV infection has been challenging. Simian Varicella Virus (SVV) infection in nonhuman primates reproduces the cardinal features of VZV infections in humans and allows the study of varicella virus pathogenesis in the natural host. In this review, we summarize our current knowledge about genomic and virion structure of varicelloviruses as well as viral pathogenesis and antiviral immune responses during acute infection, latency and reactivation. We also examine the immune evasion mechanisms developed by varicelloviruses to escape the host immune responses and the current vaccines available for protecting individuals against chickenpox and herpes zoster. RECENT FINDINGS: Data from recent studies suggest that infected T cells are important for viral dissemination to the cutaneous sites of infection as well as site of latency and that a viral latency-associated transcript might play a role in the transition from lytic infection to latency and then reactivation. SUMMARY: Recent studies have provided exciting insights into mechanisms of varicelloviruses pathogenesis such as the critical role of T cells in VZV/SVV dissemination from the respiratory mucosa to the skin and the sensory ganglia; the ability of VZV/SVV to interfere with host defense; and the identification of VLT transcripts in latently infected ganglia. However, our understanding of these phenomena remains poorly understood. Therefore, it is critical that we continue to investigate host-pathogen interactions during varicelloviruses infection. These studies will lead to a deeper understanding of VZV biology as well as novel aspects of cell biology.